“A Study On Workforce Diversity And Its Impact On Organizational Culture With Special Reference To Service Sector Organizations”- A Theoretical Framework (International Journal of Food and Nutritional Sciences, 2022)
Contemporary Organizations want to be culturally various and inclusive to be able to foster an organizational tradition. It calls for a knowledge of the function of personnel range and its courting to paintings tradition. The generation of globalization, liberalization, and privatization has revolutionized the personnel and administrative center. It has emerged as essential to have various personnel to serve the want of customers. The survey of Employees' and HR Managers' perceptions was carried to know the facts about workforce diversity and its impact on organizational culture in Service Sector organizations. Thus, the researcher has used the descriptive research design to well prior planned sample size of the employees and HR Managers, estimate of sample size from the population, and clearly defined hypotheses of the study. The researcher has tried to test it through the data collected and interpreted by testing the hypothesis through Structural Equational Modelling.